Subcortical Brain Volumes Relate to Neurocognition in First-Episode Schizophrenia, Bipolar Disorder, Major Depression Disorder, and Healthy Controls - Shi, Jing; Guo, Hua; Liu, Sijia; Xue, Wei; Fan, Fengmei; Li, Hui; Fan, Hongzhen; An, Huimei; Wang, Zhiren; Tan, Shuping; Yang, Fude; Tan, Yunlong (Frontiers in Psychiatry, 2022)
Objective: To explore differences and similarities in relationships between subcortical structure volumes and neurocognition among the four subject groups, including first episode schizophrenia (FES), bipolar disorder(BD), major depression disorder (MDD) and healthy controls (HCs). Methods: We presented findings from subcortical volumes and neurocognitive analyses of 244 subjects (109patients with FES; 63 patients with BD, 30 patients with MDD and 42 HCs). Using the FreeSurfer software, volumes of 16 selected subcortical structures were automatically segmented and analyzed for relationships with results from 7 neurocognitive tests from the MATRICS (Measurement and Treatment Research to Improve Cognition in Schizophrenia) Cognitive Consensus Battery (MCCB). Results: larger left lateral ventricle volumes in FES and BD, reduced left/right hippocampus and amygdala volumes in FES , and lower left/right amygdala volumes in BD and MDD were presented compared to HCs, and both FES and BD had a lower left/right amygdale volume than MDD; a comprehensive impairment in 7 cognitive dimensions was found in patients with FES, patients with BD had impairment in five cognitive dimensions and only two cognitive dimensions were damaged in patients with MDD; significant relationships were found between subcortical volumes and neurocognition in FES and in BD, but not in MDD and HCs; besides age and years of education, some subcortical volumes can predict neurocognitive performances variance. Conclusion: The different degree of subcortical volume damage may contribute to the differences of cognitive impairment among the three psychiatric diseases.